2021
DOI: 10.2147/jir.s287242
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Apoptosis and Suppressing Inflammatory Reactions in Synovial Fibroblasts are Two Important Ways for Guizhi-Shaoyao-Zhimu Decoction Against Rheumatoid Arthritis

Abstract: Background and Objectives Guizhi-Shaoyao-Zhimu decoction (GSZD) is often applied to control rheumatoid arthritis (RA), gout, osteoarthritis, etc. In this study, bioinformatic analysis and experimental verification were used to uncover the integral mechanism profile of GSZD against RA. Materials and Methods The chemical compositions of GSZD were identified by UPLC-QTOF-MS/MS. MH7A cell model was established to screen active compounds in GSZD, and potential targets of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Previous studies reported that inflammatory cytokines like members of the tumor necrosis factor (TNF)-superfamily could change the tumor microenvironment and promote the progression of colorectal cancer through activation of EMT. These pro-inflammatory mediators are modulated via the transcription factor NF-kB (113)(114)(115)(116). It has also been reported that focal adhesion kinase (FAK) associated with NF-kB regulates the cancer cells capacity of survival, invasiveness, and metastasis (117)(118)(119)(120).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Previous studies reported that inflammatory cytokines like members of the tumor necrosis factor (TNF)-superfamily could change the tumor microenvironment and promote the progression of colorectal cancer through activation of EMT. These pro-inflammatory mediators are modulated via the transcription factor NF-kB (113)(114)(115)(116). It has also been reported that focal adhesion kinase (FAK) associated with NF-kB regulates the cancer cells capacity of survival, invasiveness, and metastasis (117)(118)(119)(120).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The PC12 cells were seeded into a confocal laser dish and treated as previously described [16]. At the end of the intervention, the cells were washed with precooled PBS for 3 times and then fixed with paraformaldehyde without methanol for 20 min.…”
Section: Immunofluorescence Assay Of Nrf2 Nuclear Translocationmentioning
confidence: 99%
“…Mitochondrial membrane potential (MOMP, ΔΨm) decline is considered to be an early characteristics of apoptosis cells [16,19]. In addition, MOMP is of great significance in maintaining the normal physiological function of mitochondria, and the decrease of MOMP is often used as an important indicator of mitochondrial dysfunction.…”
Section: Cpm Suppressed Apoptosis In H 2 O 2 -Treated Pc12 Cellsmentioning
confidence: 99%
“…10 , 11 In modern times, HTD is often used to treat gastrointestinal bleeding, chronic UC, gastrointestinal tumor and so on. 12 , 13 However, the active compounds and mechanism of HTD for the treatment of UC are still not clear.…”
Section: Introductionmentioning
confidence: 99%